2012
DOI: 10.1002/anie.201108738
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometalated Ruthenium(II) Complexes as Near‐IR Sensitizers for High Efficiency Dye‐Sensitized Solar Cells

Abstract: Dye-sensitized solar cells (DSSCs) based on nanocrystalline TiO 2 films have attracted considerable attention because of their great potential in terms of low fabrication costs and high solar-light-to-electricity conversion efficiency. [1] Extensive efforts have been focused on the development of new, highly efficient sensitizers, as they play a critical role in cell performance. Sensitizers exhibiting absorption over a wide range of the solar spectrum and a high molecular extinction coefficient have been inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 35 publications
3
74
0
1
Order By: Relevance
“…16,17,19,[107][108][109] Additionally, cyclometalated bridging ligands enhance the electronic coupling between the redox centers in mixed-valent Ru/Ru complexes [110][111][112] and Ru/organic hybrid structures. [113][114][115][116] Despite the large variety of cyclometalated polypyridine ruthenium complexes synthesized up-to-date, however, no phosphorescence comparable to [Ru(bpy) 3 ] 2+ has yet been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…16,17,19,[107][108][109] Additionally, cyclometalated bridging ligands enhance the electronic coupling between the redox centers in mixed-valent Ru/Ru complexes [110][111][112] and Ru/organic hybrid structures. [113][114][115][116] Despite the large variety of cyclometalated polypyridine ruthenium complexes synthesized up-to-date, however, no phosphorescence comparable to [Ru(bpy) 3 ] 2+ has yet been achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Funaki investigated the possibility to maintain the same terpyridine ligand of Black Dye, tctpy, substituting two thiocyanates with a series of C ^ N bidentate ligands ( 30 in Figure 24) [116,117,118]. These complexes were designed in order to utilize ancillary ligands with stronger donor properties with respect to thiocyanates in order to destabilize the t 2 g HOMO orbital, to reduce the band gap and to harness lower energy regions of the solar spectrum.…”
Section: Modifications Of Black Dye and Structure-properties Relatmentioning
confidence: 99%
“…Furthermore, in 2012, Funaki et al [ 82 ] reported on a cyclometalated ruthenium compound of 2-phenylpyrimidine containing terpyridine and NCS ligands as ancillary ligands 9.32 as dye-sensitized solar cells. The dye-sensitized solar cells sensitized with the 2-phenylpyrimidine compound 9.32 show 10.7 % effi ciency, which is higher than the N749 ( 9.40 ) benchmark (10.1 %) as shown in Fig.…”
Section: Dye-sensitized Solar Cellsmentioning
confidence: 99%